Low-temperature, high-mobility, solution-processed metal oxide semiconductors fabricated with oxygen radical assisted perchlorate aqueous precursors. Issue 48 (31st May 2017) - Gao, Peixiong; Lan, Linfeng; Lin, Zhenguo; Sun, Sheng; Li, Yuzhi; Song, Wei; Song, Erlong; Zhang, Peng; Peng, Junbiao
Abstract : In this report, a simple and general chemical route for fabricating MO semiconducting films at a relatively low temperature without any fuel additives or special annealing steps was demonstrated. Abstract : In this report, a simple and general chemical route for fabricating MO semiconducting films at a relatively low temperature without any fuel additives or special annealing steps was demonstrated. The precursor, which consisted of perchlorate, nitrate, and water, is easily converted into In2 O3 at an annealing temperature of 250 °C due to oxygen radical assisted decomposition and generation of a large amount of heat. It is found that perchlorate salt can decompose and form an oxide film with high quality at a lower temperature when assisted by nitrate salt. The optimized In2 O3 –TFT fabricated via this precursor exhibits a saturation mobility of 14.5 cm 2 V −1 s −1 . Furthermore, this approach has been expanded to the fabrication of ZnO films and attained improved performance, indicating its universality.